Papular elastorrhexis: clinical perspectives - Sezer, Engin; Durmaz, Emel Ozturk; Sahin, Sedef (DOVE MEDICAL PRESS LTD, 2018)
First described by Bordas in 1987, papular elastorrhexis (PE) is a rare elastic fiber disorder of the skin characterized by multiple, discrete, asymptomatic, firm, nonfollicular, monomorphous, 1-5 mm, circumscribed, hypopigmented, oval to round papules, symmetrically distributed on the chest, abdomen, back, shoulders, arms, and thighs. The onset of the condition is usually in the first or second decade of life. PE appears to be an exceedingly rare entity, with 33 cases reported in the literature until now. However, the disorder might be underestimated probably because of its subtlety, asymptomatic course, and benign nature of clinical alterations, which can easily be confused with other dermatoses such as acne scars. Clinical and histopathological differential diagnosis of PE is broad and includes papular acne scars, eruptive collagenoma, disseminated lenticular dermatofibrosis (as a component of Buschke-Ollendorff syndrome), white fibrous papulosis of the neck, pseudoxanthoma elasticum, pseudoxanthoma elasticum-like papillary dermal elastolysis, middermal elastolysis, and perifollicular elastolysis. Treatment of PE is a matter of debate and no reliable curative option exists.
Keywords: papular elastorrhexis; elastic fibers; connective tissue